(untitled) (Fiep Bulletin - online, 2011)
The evaluation of quality of work life through quantitative methods has become more intense recently. Opposite to what it may seem, such practice was launched in the seventieth decade with Hackman and Oldham. The current study aims to build a criticism to Hackman and Oldham’s model of quality of work life. In order to measure quality of work life, the aforementioned authors have created a score named Motivating Potential Score. The indicators that compose the Motivating Potential Score are ramifications of satisfaction at the work environment. It is assumed that Hackman and Oldham have been the pioneers in the quantification of the evaluation instruments of quality of work life, but have not been concerned with studying the labor environment itself, taking only the behavioral approach of the workers into account. Although it is an important aspect at the working environment, quality of work life transcends the individual’s satisfaction.